Lead Exposure Is Related to Impairment of Aortic Elasticity Parameters. Issue 11 (27th September 2014) - Ozturk, Mujgan T.; Yavuz, Bunyamin; Ozkan, Selcuk; Ayturk, Mehmet; Akkan, Tolga; Ozkan, Esin; Tutkun, Engin; Yılmaz, Ömer H.
<x xml:space="preserve">Abstract</x> Arterial hypertension is one of the physical complications of chronic lead exposure. Hypertension has effects on aortic elastic properties. The aim of this study was to evaluate the aortic elastic properties in workers occupationally exposed to lead. Forty‐one workers who were exposed to lead and 39 healthy controls were included in the study. All patients underwent transthoracic echocardiography for detecting aortic elastic parameters. There were no differences in baseline characteristics between the lead‐exposure group and controls. Aortic strain (9.4%±4.5% vs 12.4%±4.2%, P=.004) and aortic distensibility (0.45±0.21 cm2/dyn vs 0.55±0.20 cm2/dyn, P=.046) were decreased in patients with lead exposure compared with controls. There was a negative significant weak correlation between aortic strain and (r=−0.294, P=.008) lead levels. There was no significant correlation between aortic distensibility and any other echocardiographic parameters. This study suggests that chronic exposure to lead is related to impairment of aortic elasticity parameters.